The Law Enforcement Against The Abuse Of Dominant Position By The E-Commerce Platform Shopee - Rochela Amalia Narindra; Heru Sugiyono (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
This study examines the enforcement of competition law against the alleged abuse of dominant position by Shopee in the delivery service sector, as reflected in Case Number 04/KPPU-I/2024. Shopee is suspected of prioritizing its affiliated service, Shopee Express, leading to discriminatory practices that disadvantage independent delivery service providers. Using a normative juridical method with a statutory and case approach, the study finds that such practices potentially violate Article 19(d) and Article 25(1) of Law Number 5 of 1999. Legal protection for independent businesses can be provided preventively through regulations prohibiting discriminatory practices and repressively through law enforcement mechanisms by KPPU or civil lawsuits. The findings highlight the importance of strengthening regulations, consistent law enforcement, and legal education to ensure fair competition and safeguard consumer interests